Journal of Disaster Science and Management - Tsukahara, Kenichi; Meguro, Kimiro; Yoon, Dong Keun.; Cheong, Tae Sung.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer.)
The Journal of Disaster Science and Management (JDSM) is a peer-reviewed journal dedicated to advancing knowledge in the field of disaster science and management. The Journal of Disaster Science and Management welcomes original research and review articles addressing on a wide range of topics related to disaster risk reduction. The journal aims to disseminate high quality research that contributes to the understanding of disaster risks and the improvement of disaster risk reduction policies, such as mitigation, preparedness, response, and recovery. .
Keywords: Earth sciences; Geography; Earth sciences; Geography; Earth Sciences; Geography; Earth and Environmental Sciences